Optimization of coffee (Coffea arabica) transformation parameters using uidA and hpt genes: effect of osmotic pre-treatment, helium pressure and target distance - Gatica, Andrés M (2009)
The aim of this work was to optimize the biolistic delivery parameters that affect the DNA delivery and stable expression of marker genes into coffee tissues (Coffea arabica. L. cvs. Caturra and Catuaí). The effect of osmotic preculture length, osmotic concentration of medium, Helium pressure and target distance on transient expression of the uidA gene in coffee leaves and somatic embryos were tested. The highest transient uidA expression was obtained when Caturra (18.3±2.8) and Catuaí (6.8±2.0) leaves and Catuaí embryos (80.0±7.4) were cultured for 5h on Yasuda medium complemented with 0.5M Mannitol +0.5M Sorbitol. The combination of 1100psi and a target distance of 9cm resulted in the highest number of blue spots per Caturra leaf segment (23.6±3.9), whereas for the Catuaí variety the combination of 1100psi and a target distance of six (10.2±1.9) and nine (8.2±1.9) cm gave the highest number of blue spots per leaf segment. The optimized protocol was tested with pCAMBIA 1 301 (uidA gene and the hpt gene), pCAMBIA 1 305.2 (uidA version GUSPlus ™ and the hpt gene) and pCAMBIA 1 301-BAR (uidA gene and the bar gene). The highest number of blue spots was obtained when Caturra (54.6±5.7) and Catuaí (28.9±4.3) leaves were bombarded with pCAMBIA 1 305.2. Selection of bombarded coffee tissues with 100mg/l hygromicyn caused the oxidation of tissues.